Needs Analysis of Uterine Involution Phantoom - Novianti, Lily; Komariah, Nurul (Institute Of Computer Science (IOCS), 2024)
This study aims to determine whether the development of a uterine involution phantom is needed in the Midwifery Department, Ministry Health Polytechnic of Palembang. This research is quantitative research with a research instrument in the form of a questionnaire. Filling out the questionnaire was carried out by fourth semester students who had passed the postpartum midwifery care and breastfeeding course. Almost all the statements the majority of respondents strongly agree. In the statement “The phantom needed is a phantom that can be palpated at the height of the uterine fundus according to the postpartum physiological age”. In the statement